Sleep endoscopy as a complementary diagnostic method for snoring and sleep apnea - Mota,Dalila Araújo (2022)
ABSTRACT Obstructive sleep apnea is a disorder characterized by complete or incomplete and recurrent upper airway collapse induced by sleep. Several diagnostic methods for obstructive sleep apnea are used, but only sleep endoscopy allows an endoscopic assessment of pharyngeal collapse during sedation. It is essential to carry out sleep endoscopy following a systematic institutional protocol, in preestablished stages, to ensure better reproducibility and reliability of the results found. Sleep endoscopy has few limitations and is a safe test, with a low risk of complications.